2020
DOI: 10.1080/13546805.2020.1715932
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous experiences are more prevalent among highly suggestible individuals who are also highly dissociative

Abstract: Introduction:Predictive coding models propose that high hypnotic suggestibility confers a predisposition to hallucinate due to an elevated propensity to weight perceptual beliefs (priors) over sensory evidence. Multiple lines of research corroborate this prediction and demonstrate a link between hypnotic suggestibility and proneness to anomalous perceptual states. However, such effects might be moderated by dissociative tendencies, which seem to account for heterogeneity in high hypnotic suggestibility. We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…Eles ocorrem mais intensamente em indivíduos com personalidade propensa à fantasia, que se utilizam desse artifício para lidar com a solidão ou o isolamento, ou para fugir de ambientes aversivos, podendo ser bem ou mal adaptativos (Somer, 2002). É sabido também que indivíduos sugestionáveis e com uma alta predisposição para quadros dissociativos exibem uma maior propensão para a manifestação de diversas EA, incluindo as de natureza alucinatória (Acunzo, Cardeña & Terhune, 2020).…”
Section: Discussionunclassified
“…Eles ocorrem mais intensamente em indivíduos com personalidade propensa à fantasia, que se utilizam desse artifício para lidar com a solidão ou o isolamento, ou para fugir de ambientes aversivos, podendo ser bem ou mal adaptativos (Somer, 2002). É sabido também que indivíduos sugestionáveis e com uma alta predisposição para quadros dissociativos exibem uma maior propensão para a manifestação de diversas EA, incluindo as de natureza alucinatória (Acunzo, Cardeña & Terhune, 2020).…”
Section: Discussionunclassified
“…Multiple studies have similarly observed reduced PPI in highly suggestible participants (Levin et al, 2011;Lichtenberg et al, 2008;Storozheva et al, 2018). Another study observed the converse (De Pascalis & Russo, 2013), which may be attributable to heterogeneity in dissociative tendencies in highly suggestible individuals (Terhune et al, 2011b; see also Acunzo et al, 2020). The germane construct of self-transcendence (Cloninger et al, 1993;Cardeña & Terhune, 2014;Grabe et al, 1999) also negatively correlates with the magnitude of PPI (Takahashi et al, 2012).…”
Section: Sensory Gating and Dissociationmentioning
confidence: 94%
“…Dissociation is probably the clinical variable related to anomalous experiences that is most commonly investigated in relation to this kind of hallucinatory episode (Jinks, 2019). Many studies have concluded that people with anomalous experiences (outside the psychopathological context) also showed high levels of dissociation (Cardeña & Carlson, 2011;Acunzo et al, 2020). However, this dissociation is not yet clear because there are other studies which did not show statistically significant summaries when the same hypotheses were tested (Vencio et al, 2018).…”
Section: Anomalous Experiences and Psychotic Symptomsmentioning
confidence: 99%